Operation drain the swamp - Andrzejewski, Adam (Encounter broadsides., 2018)
"President Donald J. Trump said he wants to "drain the swamp." But is it a swamp or an ocean? It's about time the American people had some hard facts regarding the federal bureaucracy. In Operation Drain the Swamp, we expose all of it. We showcase who receives how much, where they work, and what they do. Most importantly, we reveal how much these bureaucrats cost the American taxpayer. During the 2016 presidential election, the supporters of Donald Trump on the right - and even those supporting Bernie Sanders on the left - felt that the "system was rigged" for insiders. Now, we highlight the facts and stories to prove it. In Operation Drain the Swamp, we offer a step-by-step guide to civil service reforms"--